2021
DOI: 10.1128/spectrum.01537-21
|View full text |Cite
|
Sign up to set email alerts
|

Broad-Spectrum In Vitro Antiviral Activity of ODBG-P-RVn: An Orally-Available, Lipid-Modified Monophosphate Prodrug of Remdesivir Parent Nucleoside (GS-441524)

Abstract: While remdesivir remains one of the few drugs approved by the FDA to treat coronavirus disease 2019 (COVID-19), its intravenous route of administration limits its use to hospital settings. Optimizing the stability and absorption of remdesivir may lead to a more accessible and clinically potent therapeutic.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 22 publications
0
23
0
Order By: Relevance
“…We have repeatedly shown that remdesivir efficiently inhibits MV dissemination at half-maximal inhibitory concentrations below 180 nM, regardless if wild-type-based viruses or vaccine-strain-based viruses were used. In line with this, Lo et al estimated the IC 50 of remdesivir against MV infection in HeLa cells at 37 nM, in VeroE6 cells at 5 µM, in NCl-H358 cells at 25 nM and in HSAEC1-KT cells at 63 nM, using an rMV EZ EGFP(3) reporter-based assay [41,42]. Our assay resembles the early dissemination phase and mimics in vivo cell-to-cell viral spread instead of cell-free virus production.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…We have repeatedly shown that remdesivir efficiently inhibits MV dissemination at half-maximal inhibitory concentrations below 180 nM, regardless if wild-type-based viruses or vaccine-strain-based viruses were used. In line with this, Lo et al estimated the IC 50 of remdesivir against MV infection in HeLa cells at 37 nM, in VeroE6 cells at 5 µM, in NCl-H358 cells at 25 nM and in HSAEC1-KT cells at 63 nM, using an rMV EZ EGFP(3) reporter-based assay [41,42]. Our assay resembles the early dissemination phase and mimics in vivo cell-to-cell viral spread instead of cell-free virus production.…”
Section: Discussionmentioning
confidence: 61%
“…Ribavirin and ribavirin-derivatives and -analogs [33][34][35][36][37][38][39][40] Ring-expanded purine nucleosides [34] Remdesivir [41,42] Favipiravir (T-705) [43,44] Derivatives of R1479 [45] Pyrazofurin [36] 3-Deazaguanine and its carbocyclic analog [36,38,40] 6-Azauridine [36] 5'-nor carbocyclic adenosine analogues [46] L-dideoxy bicyclic nucleoside analogs [47] Non-nucleoside polymerase inhibitors AS136a [48,49] ERDRP-0519 [49][50][51][52] GHP-88309 [53] Fusion and entry inhibitors Peptide inhibitors Z-D-Phe-L-Phe-L-Gly (FIP) [54][55][56][57][58] HRC-based peptides: M1, M2, M3, M4, M1EK, M2EK, M3EK, M4EK [59] HRC-lipopeptides [60][61][62][63][64] FIP-lipopeptides [64] FIP-HRC-lipopeptides [64] Nonpeptidic small molecules [65] 16677 [66] 3G [63,67] AS-48 [56][57]…”
Section: Nucleoside Analogsmentioning
confidence: 99%
See 1 more Smart Citation
“… 23 Another promising orally bioavailable remdesivir‐like prodrug candidate is ODBG‐P‐RVn. 24 It also showed efficacy on five different cell lines. 25 Along with IV remdesivir, oral Rvn prodrugs would be game‐changers in the early treatment of Covid‐19.…”
Section: Remdesivirmentioning
confidence: 93%
“…Lo et al. reported an oral ODBG-P-RVn (lipid-modified monophosphate prodrug of the remdesivir parent nucleoside GS-441524), which showed a 20-fold higher antiviral activity than GS-441524 and had an activity very similar to that of remdesivir using primary-like human small airway epithelial cells ( 69 ).…”
Section: Antiviral Effect Of Remdesivir Derivativesmentioning
confidence: 99%